A18: Risk Factors for Symptomatic Avascular Necrosis in Childhood‐Onset Systemic Lupus Erythematous. Issue 11 (March 2014) - Yang, Yelin; Kumar, Sathish; Silverman, Earl D.; Levy, Deborah M.
Abstract : Background/Purpose: Childhood‐onset systemic lupus erythematous (cSLE) has a more severe clinical course with higher disease activity and involvement of major organs compared to adult‐onset SLE. Avascular necrosis (AVN) is a significant morbidity causing pain and disability, sometimes requiring joint replacement surgery. Our objective was to examine the frequency and risk factors for symptomatic AVN in cSLE. Methods: A single center matched case‐control design was used. 617 patients with cSLE followed at SickKids Lupus Clinic between July 1982 and June 2013 were included in the study. The AVN cohort consisted of 37 patients identified with clinical findings of symptomatic AVN and diagnosis confirmed by one or more imaging modalities. Three controls were matched to each AVN patient by date and age at diagnosis (± 1 year). Baseline clinical, laboratory and treatment characteristics were compared between the patients with AVN and the controls by univariate analyses and if statistically significant, were included in a multivariable logistic regression model. Results: A total of 37/617 (6%) patients developed symptomatic AVN during follow‐up at SickKids. The majority was female (30/37, 81%) and of Asian descent (20/37, 54%). The mean age at diagnosis was 16.1 years (±2.1), with median time to AVN of 1.52 years. Only 2/37 (5%) of patients developed AVN prior to the onset of puberty. The hip was the most commonly involved joint (26/37, 70%) with bilateral involvement in 49% (18/37) of patients. Compared to the matched non‐AVN cohort, patients with AVN had higher incidence of CNS disease (p = 0.003), nephritis (p < 0.001), acute or chronic renal failure (p = 0.029), but less frequent photosensitivity (p = 0.006). Patients with AVN also required greater cumulative prednisone from cSLE diagnosis to AVN (364 ± 53 vs. 232 ± 36 mg/kg, p < 0.001), higher prednisone dose at time of AVN diagnosis (±3 months, 0.30 ± 0.25 vs. 0.19 ± 0.24 mg/kg, p = 0.012), maximal daily prednisone dose (1.25 ± 0.36 vs. 0.71 ± 0.53 mg/kg, p < 0.001) and more frequent use of pulse methylprednisolone therapy (39% vs. 10%, p < 0.001). The median prednisone dose at time of AVN was 0.27 vs. 0.09 mg/kg. Multivariable regression analysis confirmed nephritis, CNS disease, maximal daily prednisone dose and use of pulse methylprednisolone as significant predictors of symptomatic AVN development. Overall disease activity from SLE diagnosis to AVN diagnosis as measured by adjusted mean SLEDAI was not significantly different (6310 ± 976 vs. 4994 ± 440, p = 0.165). Conclusion: cSLE patients with severe organ involvement including nephritis and CNS disease, higher maximal daily dose of prednisone, and more frequent use of pulse methylprednisolone are more likely to develop symptomatic AVN.